Analisis Perencanaan Tebal Lapis Tambah (overlay) Cara Lenduntan Balik Dengan Metode Pd T-05-2005-B dan Pedoman Interim No.002/P/BM/2011 - Wahyudi, Danu; Pratomo, Priyo; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Roads are the transport infrastructures which play an important role in supporting the economic growth of a region. Therefore it is necessary to do maintenance efforts so that the roads can function optimally.One of them is by adding overlay. The selection of methods become a factor that must be considered before doing flexible pavement overlay design. It is because of improper planning can cause damaged or uneconomical construction of roads. Along with the technological advances, methods of overlay flexible pavement design based on deflection also undergone many modifications such as“Pedoman Perencanaan Tebal Lapis Tambah Perkerasan Lentur Pd T-05- 2005-B”and “Pedoman Interim Perkerasan Jalan Lentur No.002/P/BM/201”. The purpose of this research was to determine the most optimal and most efficient life cyclecost of overlay design in the roads performance improvement project of Batas Kota Metro-Gedung Dalam. From the analysis results show that the design results by using Pd T 05-2005-B were thinner than Pedoman Interim No.002/P/BM/2011. It was caused by several factors such as the analysis of traffic, temperature correction factor, and the types of materials used. The indicator value of the international roughness index (IRI) is predicated by emperical equations and the design life of 20 years, obtained the lowest lifecycle costs are the result of design methods Pd T-05-2005-B. The results of the analysis also showed that the cost at the end of the design life methods Pd T-05- 2005-B less than Pedoman Interim No.002 /P/BM / 2011. Keywords :Road, Overlay, Life Cycle Cost